Incidencia del tabaquismo en estudiantes de la Escuela de Ciencias Médicas de la Universidad Técnica de Machala, año lectivo 2011 - 2012 - Celi Romero, James J. (2012)
The use of tobacco is one of the principal problems of health, and its reduction should be one of the main objectives of the ministry of health in our country. University students show the high incidences of tobacco use. The objective was to determine tobacco use of students from the School of Medical Sciences at Machala Technical University.